Głos z „pustej przestrzeni”. O recepcji debiutu Yahyi Hassana w Danii - Schab, Sylwia Izabela (Folia Scandinavica Posnaniensia, 2016)
The article attempts to analyze the reaction to the debut of the Danish poet of Palestinian descent Yahya Hassan (Yahya Hassan. Digte, 2013) among literary reviewers as well as in the Danish society. The impulse to write on this topic came after the nomination of Yahya Hassan for the Polish literary prize European Poet of Freedom 2016. The main aim is to explain the extraordinary fame as a writer and as a public person he gained already in the month of his literary debut (100.000 sold books in two months). The analyze will be focused on two fields of interest: the reception of the poetry itself and the writer’s personae.